Peningkatan Karakter Sradha Dan Bhakti Anak Golden Age Melalui Pembuatan Yadnya Sederhana - Puspita Dewi, Ida Ayu Putu Melly; Suwedawati, Gusti Ayu Kadek Arni; Sepriani, Ni Kadek (Metta : Jurnal Ilmu Multidisiplin, 2023)
One of the impacts of the Covid-19 pandemic is the weakening of the character values of Sradha and Bakthi due to the lack of religious activities in society. This study aimed to describe improving the sraddha and bhakti characters of golden age children through making simple yadnya. The method used is qualitative, with data collection techniques using observation, interviews, and literature. The results of the study found that one pasraman, which educates golden age children, carried out activities to improve the character of sraddha and bhakti through the making of ceremonial facilities such as canang, kwangen, and ngulat tipat. The government's policy of allowing schools to reopen with various strict pro-health conditions and the obligation to maintain social distance provides Widya Pasraman Pompom Pratama wider opportunities to improve children's character even with a limited time. Collaboration between the school and parents is constructive in enhancing children's character in the future, one of which is the character values of sraddha and bhakti.